Effects of chemical reagents on the properties of fly ash based geopolymer - Norbaizurah, Rahman (2015)
Geopolymer with high calcium fly ash has a wide prospect in the field of construction, hence due to this fact, it has been significantly considered in the initiation of new era of green materials. Nevertheless, introducing high calcium fly ash in geopolymer has also created a few problems. Addition of high proportion of Ca in geopolymer has diverse effects on the reactivity of fly ash in geopolymer. Moreover, it also could hinder the polymerization process and alter the microstructure of geopolymer. It will significantly result in the high viscosity and contribute to the rapid setting time, low workability and low compressive strength performance. Therefore, alternative chemical reagents such as sodium nitrate, calcium nitrate, citric acid, sucrose and di-potassium hydrogen phosphate with dosage of 0.5 %, 1.5 % and 2.5 % were studied to overwhelm these issues in high calcium geopolymer. The effect of these admixtures on fresh geopolymer was evaluated by considering the setting time and flow table workability characteristic. Another set of parameters like degree of hydration, compressive strength, porosity, scanning electron microscopy and energy-dispersive X-ray spectroscopy tests were conducted to provide the fundamental and elemental composition information on the hardened geopolymer binder. The result shows that the increment of sodium nitrate with proportion of 0.5 % to 2.5 % by weight of fly ash considerably exhibits a prolonged initial setting time but decreased the flowability of geopolymer binder. Meanwhile, calcium nitrate and sucrose has increased the flowability of geopolymer binder while reduced the setting time. Inclusion of di-potassium hydrogen phosphate and citric acid has accelerated the setting time and reduced the flowability of geopolymer binder with the increment of the dosage. The compressive strength of geopolymer binder with the inclusion of alternative chemical reagents are all higher than control except for inclusion of calcium nitrate. Inclusion of 0.5 % alternative chemical reagents were observed to be effective as a retarder and significantly causes the extension of initial setting time. Each type of alkali cation and anion have its own effects on every stage of geopolymerization process. They play the main role in ascertaining the final structure by controlling the crystal growth and contributes to the structural development by forming alumino-silicate structures. Therefore it is concluded that the 0.5 % incorporation of alternative chemical reagents has the potential use as the chemical admixtures for geopolymer